Pengaruh Media Digital terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran PAI di SMA Negeri Sitiung Dharmasraya - saputra, abdi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2021)
Student learning outcomes in class X IPS I in PAI subjects are low due to inefficient learning media and less enthusiastic students in PAI learning. This research aims to determine the use of digital media and student learning outcomes in PAI subjects in class X IPS Sma Negeri 01 Sitiung. The method used is quantitative descriptive and all respondents in class X IPS I as population. Data collection techniques used are observation, interview, and documentation—the analytical techniques used validity test, regression test, correlation coefficient test, and determination coefficient test. The results showed that digital media in PAI learning improved students' learning outcomes, as evidenced by a simple linear regression test result of 3,840 with a significance score of 0.001. The significance value is less than the t-table of 0.05 (5%). The test results are strengthened using a coefficient of determination test with r-squere of 0.330.